ll Primo "Drone" Fotogrammetrico - Selvini, Attilio (GEOmedia, 2025)
It was the end of the century, or rather the millennium. We were in the large lecture hall of the Technical University of Stuttgart, in Keplerstra?e. Many were the participants in one of the last biennial “Photogrammetrische Woche”, governed by Carl Zeiss since the beginning. Next to me was Friedrich Ackermann, who until 1992 had been director of the Institute of Photogrammetry and was now happily retired. We had been on first name terms (duzen, in German) ever since he had been a guest of Professor Luigi Mussio and myself at the Milan Polytechnic (I talk about it in my little book “Topografi e fotogrammetri fra cronaca e storia”, published by Maggioli. “Fritz” was two years younger than me). There was a new speaker on the stage and suddenly a kind of toy with propeller engines rose into the air, a real but very small helicopter, to the amazement of those present but not of Fritz who was well aware of it.